Sikap dan Perilaku Masyarakat dalam Pencegahan Penularan Coronavirus Disease 2019 (Covid-19) di Jakarta Selatan - Muhamad Ridlo; Annisa Nelson; Moh Heri Kurniawan (Politeknik Karya Husada, 2021)
Background: The World Health Organization reports that cases of COVID-19 continue to increase every day. So that people's attitudes and behavior have a big influence in preventing the transmission of COVID-19. Purpose: to describe the attitude and behavior of the community in preventing the transmission of the 2019 coronavirus disease (COVID-19) in South Jakarta. Methods: the design in this study used a quantitative descriptive design. The sampling technique used purposive sampling with the slovin formula. Respondents totaling 295 people in the Ragunan RW 008 area. Data were collected using a questionnaire that opened 20 questions online through a form and processed using Microsoft Excel and SPSS version 23. Results: This study showed 262 respondents or (88.8%) categorized have a bad attitude in preventing the transmission of coronavirus disease 2019 (COVID-19) and 286 respondents or (96.9%) are categorized as having very good behavior in preventing coronavirus disease 2019 (COVID-19). Conclusion: the public is expected to increase and have a high awareness of attitudes in preventing the transmission of the 2019 coronavirus disease (COVID-19), in order to increase the transmission rate and break the chain of the 2019 coronavirus disease (COVID-19) in South Jakarta.